The Life Cycle of Sobolewskia sibirica (Willd.) P.W. Ball (Brassicaceae) and its Peculiarities ex situ in the Southern Crimea (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
The life cycle of rare Crimean endemic species Sobolewskia sibirica (Willd.) P.W. Ball (Brassicaceae) growing on the screes of Crimean Mountains has been studied. The ontogenesis phases and life conditions have first been revealed and life form has first been determined. Data obtained from field observation and ex situ cultivation were checked.
Keywords: the Crimea, life cycle, life form, rythm of seasonal development, Sobolewskia sibirica.